THE IMPACT OF INVESTMENT OPPORTUNITY SET AND COST OF EQUITY TOWARD FIRM VALUE MODERATED BY INFORMATION TECHNOLOGY GOVERNANCE - Diana Frederica (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The aims of this study are to analyze whether the Investment Opportunity Set (IOS) that measured by Market to Book Value of Equity (MBVE) and the Cost of Equity (CoE) that measured by Ohlson (1995) influences Firm Value that proxied by Price Book Value (PBV), whether IT Governance can moderate the influence of IOS and CoE on Firm Value. The research sample was taken using a purposive sampling method with the type of banking industry listed on the IDX in 2011-2016. The total observation is 188 which consists of 39 companies. Data is processed using the Moderating Regression Analysis (MRA) with the SPSS program. The results are that Investment Opportunity Set has a positive influence on Firm Value, Cost of Equity has a negative influence on Firm Value, IT Governance weakens the influence of IOS on Firm Value, and IT Governance does not moderate the CoE of Firm Value.